The relationship between the fat content of Svalbard reindeer in autumn and their death from starvation in winter - Tyler, N. J.C. (Rangifer, 1986)
The relationship between body fat reserves in autumn and age-specific mortality in winter were examined in Svalbard reindeer (Rangifer tarandus platyrhynchus Vrolik). Total dissectible fat (TDF) was measured in 17 females, 1-12 years of age, shot on Spitsbergen (78°N lat.) in autumn 1980-1981. TDF declined with age in reindeer 2 years and older. The youngest females which died in winter, with the exception of calves, were aged 7 years old. A direct causal link between low autumn TDF and mortality in winter seemed unlikely. Mortality was clearly associated with the degree of wear of molariform teeth. Perhaps severe tooth wear results in inefficient mastication of low quality forage and a decline in the rate of passage of digesta, thereby restricting the amount of food that reindeer can eat. A simple model of the energy balance of female Svalbard reindeer in winter shows that they must obtaine not less than about 74% of their total energy requirements from forage. Consequently, differences in the ability of individual reindeer to feed in winter are potentially more important for survival than differences in their fat content in autumn.
Keywords: body composition; energy balance; mortality; reindeer; Rangifer; starvation; Svalbard; tooth wear